IoT-Based Propane and Butane Pressure Measurement - Frabowo Prasetia; Andi Putra B (Inspiration)
Liquefied Potreleum Gas is a hydrocarbon containing two main gas components, propane, and butane, produced from oil and gas refineries Liquefied Potreleum Gas is a hydrocarbon containing two main gas components, propane, and butane, produced from oil and gas refineries. In this study, researchers will do the same thing in the IoT field but not in health monitoring but refer to Butane and Propane Gas Pressure Monitoring in LPG. Errors often occur when using an analog manometer (needle panel) when taking pressure measurements due to inaccurate measurements. There is a clear necessity for using digital manometers to ensure precise gas methane pressure measurement. The sensor receives data then the Arduino processes the data for conversion, the final results will be sent to the cloud using the esp8266 module and then forwarded to the smartphone as a monitoring user to see and also check gas conditions.